2014
DOI: 10.5603/cj.a2013.0124
|View full text |Cite
|
Sign up to set email alerts
|

Microvolt T-wave alternans in adults with complex congenital heart diseases

Abstract: 1 ± 5.9 vs. 26.3 ± 6.7, p = 0.002),, p = 0.01). Multivariate logistic regression analysis proved that pulmonary hypertension (OR = 13.7, p = 0.03), male gender (OR = 10.4, p = 0.00002)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This included clinical signs and symptoms used to screen for PAH in other populations (eg, fatigue, dyspnea, palpitations and arrhythmia, volume retention, ECG changes), which are often noted in ACHD. 21 , 29 , 30 , 31 , 32 , 33 , 34 , 35 No clinically meaningful associations between patient characteristics and clinical course or rate of newly-diagnosed PAH were identified from ACHD-QuERI data. We are cautious not to overextend this conclusion, as valid quantification of newly diagnosed PAH requires hemodynamic assessment via RHC, which was performed in a minority of patients.…”
Section: Discussionmentioning
confidence: 99%
“…This included clinical signs and symptoms used to screen for PAH in other populations (eg, fatigue, dyspnea, palpitations and arrhythmia, volume retention, ECG changes), which are often noted in ACHD. 21 , 29 , 30 , 31 , 32 , 33 , 34 , 35 No clinically meaningful associations between patient characteristics and clinical course or rate of newly-diagnosed PAH were identified from ACHD-QuERI data. We are cautious not to overextend this conclusion, as valid quantification of newly diagnosed PAH requires hemodynamic assessment via RHC, which was performed in a minority of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sudden cardiac death (SCD) mostly resulting from ventricular arrhythmia remains a cause of mortality in 19-30% of adults with congenital heart defects [4]. Prime risk factors of MVA are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…MTWA is an electrocardiographic (ECG) phenomenon displaying inhomogeneity of the myocardial repolarization process. The prognostic value of MTWA in ischemic heart diseases, heart failure, and cardiomyopathies has been demonstrated ( 16 - 19 ). Sakaki et al ( 20 ) reported that MTWA values higher than 65 microvolt were related with cardiac mortality in adult patients with left ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 99%